A Pilot Study on the Effect of Daylighting and Orientation in the Office Building: A Case of Kathmandu - Basnet, Bimala; Uprety, Sanjaya (Advances in Engineering and Technology: An International Journal, 2022)
Illuminance results in visibility of objects and daylighting is the major source of light for perceiving and carrying out certain function. Office blocks hold the space for people to perform economic task for 7-8 hours daily and humans seek comfort. Lighting the interior is a mindful job, as the space can be over lit or under lit resulting in visual discomfort and high use of energy to maintain human comfort. Quality and quantity of natural light in the indoor is guided by several factors such as climate, latitude, sky condition, site obstructions, orientation, opening design, surface reflectivity, space function etc. The study shows that the best orientation for Kathmandu is 175°N and for the building with window wall ratio greater than 60%, orientation does not play a vital role. Autodesk Ecotect 2011, has been used to simulate the building with the real case scenario in the urban context for the outmost result. The finding adds value during the early design phase and also to prepare guidelines, policies and bylaws relating to wellbeing of occupant for visually and functionally friendly interior.